A nonfullerene acceptor with a 1000 nm absorption edge enables ternary organic solar cells with improved optical and morphological properties and efficiencies over 15%. Issue 8 (28th June 2019) - Liu, Tao; Luo, Zhenghui; Chen, Yuzhong; Yang, Tao; Xiao, Yiqun; Zhang, Guangye; Ma, Ruijie; Lu, Xinhui; Zhan, Chuanlang; Zhang, Maojie; Yang, Chuluo; Li, Yongfang; et al.
Abstract : The PM7:ITC-2Cl:IXIC-4Cl-based ternary device achieved an excellent PCE of 15.37% with a energy loss of 0.42 eV. Abstract : Ternary organic solar cells (OSCs) have shown tremendous potential in improving the photovoltaic performance of single-junction OSCs. Here, a series of ternary OSCs are fabricated with PM7:ITC-2Cl as the host system and an ultra-low bandgap acceptor named IXIC-4Cl that has an absorption edge reaching 1000 nm as the third component. The optimal ternary OSC shows a power conversion efficiency (PCE) of 15.37%, which is significantly higher than those of the binary counterparts based on PM7:ITC-2Cl (13.72%) or PM7:IXIC-4Cl (12.01%). The excellent PCE is mainly attributed to the increased short-circuit current ( J SC ), which mainly arises from the complementary absorption of the third component and thus the overall broadened absorption profile. In addition, the addition of IXIC-4Cl into the PM7:ITC-2Cl binary system suppresses bimolecular recombination, improves charge dissociation and the collection efficiency, balances charge transport and reduces the domain size, which are responsible for the enhanced J SC . Noticeably, the optimized ternary device shows a PCE over 15% with a quite small energy loss, which are the best results for ternary OSCs to date. These results offer more insight into the role of an ultra-low bandgap non-fullerene acceptor as the third component in promoting the device performance of ternary OSCs.